PENGEMBANGAN SCHOOL MOBILE LEARNING PADA MATA PELAJARAN KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI DI SMK NEGERI 1 SUKASADA - Raden Ayu Kristi Kurniawati (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research was aimed to : (1) designing application of school mobile learning of KKPI subject in SMK Negeri 1 Sukasada (2) implement application school mobile learning of KKPI subject in SMK Negeri 1 Sukasada (3) studying the response of the students class XII Multimedia 2 to the application school mobile learning of KKPI subject in SMK Negeri 1 Sukasada.  The subject of this research are all student of Multimedia 2 class XII in SMK Negeri 1 Sukasada academic year 2012/2013 which are 21 peoples. This research is research and development (R&D The data collected include students’ response data towards the development of application school mobile learning with the use of Mastery Learning by descriptively. The data of students’ response were analyzed by descriptive The software is built in the form of a website for data processing. While learning the use of School Mobile Learning applications are integrated on the phone, so that the students can using the application School Mobile Learning anytime and anywhere. The system was developed by DFD (Dataflow Diagram) is used to design the system using J2ME and PHP as the programming language and MySQL for database.  The result of this research that student’ response to the application of School Mobile Learning of KKPI subject with the use of Mastery Learning are positive categorized.